Empowering Rice Farmers through Climate Adaptation Mentoring and Paddy Field-Based Agricultural Enterprise Diversification - Muallief Ummar (Bisma : Bimbingan Swadaya Masyarakat, 2025)
Climate change and land constraints pose significant threats to rice-farming communities. This study implemented Participatory Action Research (PAR) with farmers in Sawahan to co-develop and evaluate integrated strategies for Climate-Smart Agriculture (CSA) and farm diversification. Over iterative cycles, farmers and researchers collaboratively designed and tested a bundled CSA approach combining drought-tolerant rice varieties, Alternate Wetting and Drying (AWD) water management, and organic composting. This integration resulted in a 20-25% reduction in irrigation water, a 12% increase in yield, and improved soil health. Concurrently, a rice-duck integration system was piloted, demonstrating effective pest and weed control while providing a profitable secondary income from duck and egg sales. The process critically fostered farmer-led innovation, including the cultivation of high-value crops on paddy dykes. Key findings reveal that technical solutions must be synergistically bundled and coupled with economic diversification to build systemic resilience. More importantly, the PAR methodology successfully catalyzed a shift from passive technology adoption to active community-led adaptation, as evidenced by the emergence of a spontaneous farmer-to-farmer learning network. The study concludes that empowering farmers through participatory co-learning is fundamental to developing locally relevant, adaptive, and resilient farming systems capable of weathering climatic and economic uncertainties